(untitled) (Research, Society and Development, 2021)
Objective: To know the experiences of obstetric violence among postpartum women. Methodology: Qualitative study conducted through 12 interviews with women hospitalized in two maternity hospitals at usual risk in the capital of Alagoas, Maceió. Result: In the analysis of the reports, different critical factors emerged, such as: difficulty in accessing maternity hospitals, lack of professional follow-up to patients, horizontalization of childbirth, priority of medical professionals’ wishes contrary to maternal ones, verbal violence, lack of humanization, lack of perception of the violence experienced, among others. Final Considerations: The experiences reported indicated several forms of obstetric violence, in addition to the use of obstetric practices considered harmful, ineffective, without scientific evidence or performed inappropriately. The study points out that there are significant flaws in the care processes in assisting women, evidencing the disrespect for their rights.